2016
DOI: 10.1093/jac/dkw447
|View full text |Cite
|
Sign up to set email alerts
|

In vitroactivity of gentamicin as an adjunct to penicillin against biofilm group BStreptococcus

Abstract: These in vitro investigations show activity of 12.5 mg/L gentamicin, alone or as an adjunct to penicillin, against four strains of biofilm GBS. This concentration cannot be achieved in bone with systemic administration, but can be reached if administered locally. The combination of systemic penicillin plus local gentamicin indicates a potential application in orthopaedic-device-associated GBS infections. Studies with a larger number of strains are required to confirm our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…It was reported that some clonal complexes of S. agalactiae were shared between cows and farm personnel, indicating the zoonotic potential of this species (Cobo-Angel et al, 2019). These pathogens are also producers of biofilms (Gomes et al, 2016;Reinoso, 2017;Alves-Barroco et al, 2019;Horiuk et al, 2019), and this virulence characteristic has been associated with persistent infections and development of antibiotic resistance (Olson et al, 2002;Ruppen et al, 2017).…”
Section: Clinical and Veterinary Relevance Of Pyogenic Biofilmmentioning
confidence: 99%
“…It was reported that some clonal complexes of S. agalactiae were shared between cows and farm personnel, indicating the zoonotic potential of this species (Cobo-Angel et al, 2019). These pathogens are also producers of biofilms (Gomes et al, 2016;Reinoso, 2017;Alves-Barroco et al, 2019;Horiuk et al, 2019), and this virulence characteristic has been associated with persistent infections and development of antibiotic resistance (Olson et al, 2002;Ruppen et al, 2017).…”
Section: Clinical and Veterinary Relevance Of Pyogenic Biofilmmentioning
confidence: 99%
“…The observed effective gentamicin doses cannot be achieved in bone tissue with systemic administration. Comparable conclusions have been made from several in vitro studies of biofilm susceptibility (21). To meet the demand for high and long-term antimicrobial bone concentrations without reaching toxic serum levels, several commercial local delivery systems are available for infectious orthopedic surgery (22).…”
Section: Discussionmentioning
confidence: 99%
“…However, Staphylococcus spp., Streptococcus spp., and Enterococcus spp. may display high-level gentamicin resistance (62,83).…”
Section: Antimicrobial Susceptibility Testing Of Biofilm Bacteriamentioning
confidence: 99%